2020
DOI: 10.1002/hpm.2980
|View full text |Cite
|
Sign up to set email alerts
|

Fine for non‐attendance in public hospitals in Denmark: A survey of non‐attenders' reasons and attitudes

Abstract: Summary Objective To investigate non‐attending patients' reasons for non‐attendance and their general and specific attitudes towards a non‐attendance fine. Data sources Non‐attenders at two hospital departments participating in a trial of fine for non‐attendance from May 2015 to January 2017. Design A quantitative questionnaire study was conducted among non‐attenders. Data collection Non‐attending patients in the intervention group were invited to complete the questionnaire. The response rate was 39% and the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Although the consultation process is open to everyone, citizens themselves rarely submit responses. Health professionals’ and patients’ views and opinions about using non-attendance fees have been understudied 22 49 50. Further studies should provide data from health professionals and patients.…”
Section: Discussionmentioning
confidence: 99%
“…Although the consultation process is open to everyone, citizens themselves rarely submit responses. Health professionals’ and patients’ views and opinions about using non-attendance fees have been understudied 22 49 50. Further studies should provide data from health professionals and patients.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Shahab I and Meili R, in a study of nonattendance in a community clinic, found that 32.6% of the respondents forgot about their appointments, with the second most common reason being declining health status (23.3%) [ 18 ]. Vaeggemose U et al, in a study of nonattendance in public hospitals, concluded that 18% of the respondents reported forgetfulness [ 19 ]. A total of 11.82% of the patients forgot about the appointments (mean waiting time until consultation was 14.17 ± 9.75 days) in our study.…”
Section: Discussionmentioning
confidence: 99%